Case Studies in Operations Research Applications of Optimal Decision Making - Murty, Katta G (Springer, 2015)
During my High School education, I had a mathematics teacher who used to prove one theorem after another in his class. In that class I got the impression that his aim, and in fact the aim of mathematics as a subject, is to maximize the number of theorems proved. After seeing what felt like close to 100 theorems, I thought of the question, what is the very first mathematical result realized by mankind? The textbook did not discuss this aspect at all. So one day, I picked up enough courage to ask the teacher about it. He thought about it for a long time, and then said that he does not know the answer, but will discuss with other colleagues and let me know. My question went up all the way to the level of the Head Master, but none of the teachers knew the answer....